Ask the Experts: Cardiovascular complications in diabetic patients. (November 2011) - Mosseri, Morris; Bhatt, Deepak L; Raz, Itamar
Morris Mosseri trained at Hadassah University Hospital (Jerusalem, Israel) and was certificated as a Cardiologist in 1987. He worked as a Research Associate at the Division of Cardiology, St. Elizabeth''s Hospital (MA, USA) from 1989 to 1991, and in Washington Hospital Center (DC, USA) in 1998. Mosseri was appointed Director of Interventional Cardiology at Hadassah in 2000 and since 2006 he is the Head of Cardiology Division in Meir Medical Center (Kfar-Sava, Israel). Significant academic activities of Mosseri include appointment as Chair of the Internal Medicine Section in the Medical School of the Hebrew University and Hadassah in 2000–2003, the Editor of the Journal of the Israel Heart Society in 1997–2002 and the Chairman of the Israeli Working Group on Interventional Cardiology from 2005 to 2009. Clinical and research areas of interest include acute coronary syndrome, interventional cardiology, the diabetic heart and cardiology in the elderly. Deepak L Bhatt is Chief of Cardiology at VA Boston Healthcare System (MA, USA) and Director of the Integrated Interventional Cardiovascular Program at Brigham and Women''s Hospital (MA, USA) and the VA Boston Healthcare System (MA, USA). Bhatt is also a Senior Investigator in the Thrombolysis In Myocardial Infarction Study Group and an Associate Professor of Medicine at Harvard Medical School (MA, USA). Bhatt is the current Chair of the American Heart Association – Get With The Guidelines Science Subcommittee. He is the Associate Editor for clinical trials for the American College of Cardiology''s Cardiosource. He has also served as principal investigator for numerous studies and has held leadership positions in several registries. Bhatt''s research interests include preventive cardiology, the optimal management of patients with acute coronary syndromes and advanced techniques in cardiac, cerebral and peripheral intervention. Itamar Raz holds an MD from Hadassah Medical School at the Hebrew University (Jerusalem, Israel) where he is a Professor of Internal Medicine and the Head of the Diabetes Unit at Hadassah University Hospital. Raz is also the head of the Israel National Council of Diabetes, which is responsible for formulating national policies. In addition, Raz is President of D-Cure, a nonprofit organization that promotes and funds scientific research into finding a cure and better treatments for diabetes in Israel. At Hadassah, Raz is involved in basic and clinical research and is currently leading several large international outcome diabetes studies involving the heart and kidney in diabetic patients. He has over 230 publications to his credit in professional peer-reviewed journals and serves on international advisory and editorial boards.